Bulk Photovoltaic Current Mechanisms in All-Inorganic Perovskite Multiferroic Materials - Jiazheng Chen; Guobin Ma; Boxiang Gong; Chaoyong Deng; Min Zhang; Kaixin Guo; Ruirui Cui; Yunkai Wu; Menglan Lv; Xu Wang (Nanomaterials, 2023)
After the discovery of bulk photovoltaic effect more than half a century ago, ferro-electrical and magneto-optical experiments have provided insights into various related topics, revealing above bandgap open voltages and non-central symmetrical current mechanisms. However, the nature of the photon-generated carriers responses and their microscopic mechanisms remain unclear. Here, all-inorganic perovskite Bi<semantics>0.85</semantics>Gd<semantics>0.15</semantics>Fe<semantics>1−x</semantics>Mn<semantics>x</semantics>O<semantics>3</semantics> thin films were prepared by a sol-gel process and the effects of Gd and Mn co-doped bismuth ferrites on their microtopography, grain boundries, multiferroic, and optical properties were studied. We discovered a simple “proof of principle” type new method that by one-step measuring the leakage current, one can demonstrate the value of photo generated current being the sum of ballistic current and shift current, which are combined to form the so-called bulk photovoltaic current, and can be related to the prototype intrinsic properties such as magneto-optical coupling and ferroelectric polarization. This result has significant potential influence on design principles for engineering multiferroic optoelectronic devices and future photovoltaic industry development.